Influence Of Microelement Fertilizers In Foliar Feeding Of Cotton On Changes In Cotton Boll Weight. - Davronov Qakhramonjon Anvarjonovich; Teshaboyev Nodirbek Ikromjonovich (Zien Journals, 2024)
The importance of the microfertilizer “Cafolon”, which is used to feed plants from leaves when caring for cotton, in changing the weight of one cotton boll was studied.
Keywords: cotton; agriculture; cafolon